Does cognitive aging follow an orchid and dandelion phenomenon? - Rodrigues, Emma A.; Christie, Gregory J.; Farzan, Faranak; Moreno, Sylvain (Frontiers in Aging Neuroscience, 2022)
Cognitive reserve reflects the brain’s intrinsic adaptive capacity against the neurodegenerative effects of aging. The maintenance or enhancement of the brain’s cognitive reserve plays a crucial role in mitigating the severity of pathologies associated with aging. A new movement, social prescribing, which focuses on prescribing lifestyle activities as a treatment for patients, is growing in popularity as a solution against aging pathologies. However, few studies have demonstrated a clear impact of lifestyle activities on individual cognitive health, outside of floor and ceiling effects. Understanding who benefits from which lifestyle factors remains unclear. Here, we investigated the potential effects of lifestyle activities on individuals’ cognitive health from more than 3,530 older adults using a stratification method and advanced analysis technique. Our stratification methods allowed us to observe a new result: older adults who had relatively average cognitive scores were not impacted by lifestyle factors. By comparison, older adults with very high or very low cognitive scores were highly impacted by lifestyle factors. These findings expand the orchid and dandelion theory to the aging field, regarding the biological sensitivity of individuals to harmful and protective environmental effects. Our discoveries demonstrate the role of individual differences in the aging process and its importance for social prescribing programs.